Evaluasi Kapasitas Tanki Mixing Sebagai Constraint Utama dalam Perencanaan Produksi Infusan - Adi Setiawan Saputra; Gilang Adi Winahyu; Rizky Nasrullah; Tiaradia Ihsan (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
In the infusion industry, when the capacity of processes is not balanced, it often creates production bottlenecks, especially if the mixing tank's capacity does not match the daily demand. Mixing is a key step because it prepares the large volume of solution needed for the filling process. If the mixing stage has limited capacity, it can lead to lower production output, more work-in-process inventory, and delays in meeting the production schedule. This study looks at how the mixing tank's effective capacity is the main limiting factor in the infusion production system. It uses capacity planning and the Theory of Constraints (TOC) to evaluate this. The results show that the mixing tank can only handle about 2,000 liters per day, while the daily demand is 3,000 liters, creating a backlog of 1,000 liters per day and causing downstream processes to operate at less than 70% efficiency. After making changes such as reducing cleaning time, speeding up transfer times, and reorganizing batch scheduling, the mixing capacity increased to 3,000 liters per day. This removed the bottleneck without needing extra investment. These results show that using TOC-based process improvements can help boost capacity, keep production running smoothly, and reduce the risk of missing delivery deadlines in the batch-based infusion industry.